Mass mortality of Canthigaster rostrata (Tetraodontiformes: Tetraodontidae) on the southern Costa Rican Caribbean coast - Piedra-Castro, Lilliana (2018)
In 2017 a mass mortality event of the reef fish Canthigaster rostrata was observed on the Southern Caribbean coast of Costa Rica. The 86 subjects collected, possibly juveniles, were less than 49 mm and below 2.8 g. Similar events have been reported in other Caribbean locations and may be associated with changes in sea temperature or resource exhaustion during their recruitment period.